Polities in South Asia - Shiv Lal (New Delhi, 1989)
As conceived by the SAARC meeting held at Islamabad, the years 1986 on-wards are going to witness quite new some dimensions in inter-relationships among"Polities in South Asia". Irrespective of the SAARC developments this 4-Volume set discusses threadbare constitutional, electroral and parliamentary histories of the selected seven nations--Afghanistan-Bangladesh(Vol-1); Burma-Pakistan (Vol-2); Nepal -Sri Lanka (Vol-3); and India(Vol-4).
Keywords: Afghanistan-Politics and government